Linking the impact of aspiration to host variables using the BOLUS framework: support from a rapid review - Palmer, Phyllis M.; Padilla, Aaron H. (Frontiers in Rehabilitation Sciences, 2024)
PurposeThe purpose of this rapid review was to identify the level of evidence for a previously proposed theoretical framework to assess risks associated with prandial aspiration using the host as a central theme.MethodsCovidence software was used to search two databases (PubMed and Web of Science). PEDro scale was utilized to determine the quality of individual studies. Data points were evaluated for level of support and determined to be either conclusive, suggestive, unclear, or not supportive. Within each component of the framework, data points were clustered to determine the level of evidence as strong, moderate, insufficient, or negative.ResultsThe rapid review process resulted in a limited number of publications investigating host variables impact on outcomes for patients with swallowing disorders. Overall, it yielded 937 articles, of which, upon review, 16 articles were selected for data extraction. There was a strong level of evidence to support that (a) as viscosity and density of aspirate increased, so did the likelihood of general medical complications, (b) poor oral care and oral health increase the risk of a pulmonary or general medical complication, and (c) the presence of oropharyngeal or laryngeal tubes increases the risk of a pulmonary consequence. There was moderate evidence to support the impact of amount and frequency of aspiration on outcomes. There was insufficient evidence to determine relationships for all other aspects of the BOLUS framework.ConclusionAdditional evidence to support the BOLUS framework was obtained; however, the number of studies was limited. A more thorough review such as a systematic review should be employed.